Forging people race, ethnicity, and nationality in Hispanic American and Latino/a thought - Gracia, Jorge J. E. (Latino perspectives., 2011)
"Forging People explores the way in which Hispanic American thinkers in Latin America and Latino/a philosophers in the United States have posed and thought about questions of race, ethnicity, and nationality, and how they have interpreted the most significant racial and ethnic labels used in Hispanic America in connection with issues of rights, nationalism, power, and identity. Following the first introductory chapter, each of the essays addresses one or more influential thinkers, ranging from Bartolome de Las Casas on race and the rights of Amerindians; to Simon Bolívar's struggle with questions of how to forge a nation from disparate populations; to modern and contemporary thinkers on issues of race, unity, assimilation, and diversity. Each essay carefully and clearly presents the views of key authors in their historical and philosophical context and provides brief biographical sketches and reading lists, as aids to students and other readers."Latin American philosophy has a long history of engagement with issues of race, ethnicity, and nationality. To date, however, there has been no volume that focused on the contributions of the major figures in the Latin American tradition, to illustrate their connections, and to illuminate the context in which much of their work occurred. This volume fills that gap and takes an important step in remedying this shortcoming in the existing philosophical literature, and also in the literature of related fields such as Latin American studies, ethnic studies, and the cross-disciplinary work of race, ethnicity, and nationality." --Manuel Vargas, University of San Francisco "--